2017
DOI: 10.1002/jat.3546
|View full text |Cite
|
Sign up to set email alerts
|

Maduramicin induces apoptosis and necrosis, and blocks autophagic flux in myocardial H9c2 cells

Abstract: Maduramicin, a polyether ionophore antibiotic, is widely used as an anticoccidial agent in the poultry industry. It has been reported that maduramicin may cause heart and skeletal muscle cell damage, resulting in heart failure, skeletal muscle degeneration and even death in animals and humans, if improperly used. However, the molecular mechanism behind its capability to cause death of cardiac cells is not known. Here, we show that maduramicin induced apoptosis and necrosis in rat myocardial cells (H9c2). Madur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…We herein report cytoplasmic vacuolization‐related methuosis in mammalian cell line (H9c2) induced by the toxic drug maduramicin, which frequently causes intoxication of target and nontarget animals (Britzi et al, 2017; Shimshoni et al, 2014; Singh & Gupta, 2003) as well as humans who ingested this drug accidently (Sharma et al, 2005). However, our previous findings demonstrate that apoptotic and non‐apoptotic cell death mediates maduramicin‐induced cardiotoxicity in vitro model using H9c2 cells (Chen, Chen, et al, 2018). Maduramicin‐triggered non‐apoptosis puzzled us for a long period until we found this unique phenotype “cytoplasmic vacuolization,” which occurred along with cytotoxicity.…”
Section: Discussionmentioning
confidence: 89%
“…We herein report cytoplasmic vacuolization‐related methuosis in mammalian cell line (H9c2) induced by the toxic drug maduramicin, which frequently causes intoxication of target and nontarget animals (Britzi et al, 2017; Shimshoni et al, 2014; Singh & Gupta, 2003) as well as humans who ingested this drug accidently (Sharma et al, 2005). However, our previous findings demonstrate that apoptotic and non‐apoptotic cell death mediates maduramicin‐induced cardiotoxicity in vitro model using H9c2 cells (Chen, Chen, et al, 2018). Maduramicin‐triggered non‐apoptosis puzzled us for a long period until we found this unique phenotype “cytoplasmic vacuolization,” which occurred along with cytotoxicity.…”
Section: Discussionmentioning
confidence: 89%
“…The median survival time exceeded 40 days for both strains, compared to only 27 days in the group receiving the free drug (Rajendran et al, 2018). Following the same line, maduramicin, an ionophore antibiotic with good gametocytocidal activity (Sun et al, 2014) but of high toxicity and lipophilic character (Chen et al, 2018), was incorporated in SPC‐Chol and PEGylated liposomes, (Raza et al, 2018). The PEGylated liposomal formulations (Table 1) not only prevented the unwanted toxic side effects of this drug but also showed IC 50 values of 1.25 and 1.20 ng/mL in P .…”
Section: Nanomaterials In the Fight Against Malariamentioning
confidence: 99%
“…In chickens, the approved dose of maduramicin is 5 mg/kg [ 70 ], but such a dose can be toxic in chickens. Five ppm and 10 ppm doses of maduramicin were applied to chickens, and they were considered safe during the first seven days of the administration.…”
Section: Toxicity Of Ionophoresmentioning
confidence: 99%
“…Using rat myocardial cell lines, Chen et al showed that maduramicin induced apoptosis via caspase-dependent and independent mechanisms, necrosis, and autophagy in a dose-dependent manner [ 70 ]. These in vitro studies showed that the mechanisms of maduramicin toxicity could follow the same molecular patterns in myocardial cells.…”
Section: Toxicity Of Ionophoresmentioning
confidence: 99%